Improvement of energy density in single stator interior permanent magnet using double stator topology - Raja Othman, Raja Nor Firdaus Kashfi; Misron, Norhisam; Vaithilingam, Chockalingam Aravind; Nirei, Masami; Wakiwaka, Hiroyuki (Hindawi Publishing Corporation, 2014)
The paper presents the energy density improvement using magnetic circuit analysis of the interior permanent magnet motor. The leakage flux from the conventional structure is improved with modified magnetic circuit to improve the energy and thereby the torque value. This is approached with a double stator structure design. The proposed structure is investigated with two design variations, namely, the double stator with thin pole shoe and the double stator with thick pole shoe motors. Variations in the mechanical parameters of the all the developed models are analyzed through the finite element analysis tool. In all investigations the magnetic source is fixed in both the permanent magnet volume and coil magnetomotive force, respectively, as 400 mm3 per each pole and 480 Ampere turns per pole. From the analysis the best fit magnetic structure based on the torque characteristics is derived and is fabricated for the same volume as that of the conventional structure for performance evaluations. It is found out that there is improvement on the motor constant square density for the proposed improved magnetic circuit through the best fit double stator with thick pole shoe by about 83.66% greater than that of the conventional structure.